FIRST RECORD OF COLCHICUM TRIPHYLLUM (COLCHICACEAE) FROM HIGH ALTITUDE IN NORTHEASTERN ALGERIA (Acta Horti Botanici Bucurestiensis, 2024)
We report the first sighting of Colchicum triphyllum Kunze, from the Belezma National Park (BNP, Batna, Northeastern Algeria) at 1802 m a.s.l. (Latitude 35°33' N, Longitude 5°58' E). C. triphyllum is known to be present in the North of Algeria, but its presence had not been confirmed at high altitudes. The observation of a population of 139 flowering individuals and 47 individuals at vegetative growth had taken place in April 2023 while conducting ecological surveys. The species is suggested to be distributed at elevations ranging from sea level to 1500 m a.s.l. This finding of a population of C. triphyllum at 1802 m a.s.l. in the BNP represents a new high-altitude register for this species. The paper describes its distribution, biology, morphology, ecology, phenology, and also its medicinal properties. Conservation efforts may be necessary to protect and increase the population size of this rare species.
Keywords: Colchicum triphyllum; Belezma National Park; Distribution; Ecology; Conservation